Penolakan Permohonan Perceraian Akibat Perbedaan Identitas dan Perkawinan Dianggap tidak Pernah Ada Serta Akibatnya Terhadap Anak yang Dilahirkan - Setiadi, Monica; Yustikarini, Meliyana (Universitas Ekasakti, 2023)
Divorce applications can be made if they meet the requirements for divorce. In this case, divorce that has met the requirements cannot be carried out, because there is a difference in identity in the marriage book with the Identity Card. The purpose of this study is to provide education on steps that can be taken if there is a mistaken identity in the marriage book to be able to file a divorce and the status and position of children born from the marriage. Because in this case the parties did not take any action assuming that they never entered into marriage. This certainly makes a problem because it will have an impact on the status of the couple, marital property and children born from the marriage. The result of this study is that differences in identity can be changed by the Office of Religious Affairs as stipulated in Article 37 of the Regulation of the Minister of Religious Affairs Number 20 of 2019 concerning Marriage Registration, so there is no need to remarry with their true identity and a divorce application can be submitted. Marital property in the form of joint property can be determined by each party for its share. Children born remain legitimate children because marriages that are presumed to have never existed do not apply retroactively to children born.